Die satirische Kurzprosa Heinrich Bölls - Friedrichsmeyer, Erhard (UNC Studies in the Germanic Languages and Literatures, 1981)
This work is a structural analysis of Böll's short satirical prose, which is generally acclaimed as his most successful fiction. The author shows how Böll shifted the form and structure of his satirical writing over time in response to changing political and social conditions, focusing on Böll's changing conception of satire from the early 1950s to the 1970s, his use of satirical conventions, and his personal, unmistakable signature as a satirist. The investigation is rounded out by synoptic chapters on the proto-satirical texts of the late forties, on the lines of separation between satirical and parabolic texts, and on the longer satirical narratives.